(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This study explores the study habits of senior secondary school students. The study is descriptive-survey in nature. The stratified random sampling technique was used to select the sample of 100 senior secondary schools students of Baramulla district. For data collection process, the investigator used the tool of study habits inventory by Mukhopadhyay & Sansanwal (2011).The major findings of the study were: (i) mean scores of study habits of private and government senior secondary school students differ significantly (ii) mean scores of study habits of male and female senior secondary school students differ significantly.